2021
DOI: 10.3389/fpls.2021.757997
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control and High Temperature Effects on Starch Biosynthesis and Grain Quality in Rice

Abstract: Grain quality is one of the key targets to be improved for rice breeders and covers cooking, eating, nutritional, appearance, milling, and sensory properties. Cooking and eating quality are mostly of concern to consumers and mainly determined by starch structure and composition. Although many starch synthesis enzymes have been identified and starch synthesis system has been established for a long time, novel functions of some starch synthesis genes have continually been found, and many important regulatory fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 124 publications
1
10
0
Order By: Relevance
“…High temperature affects starch accumulation in rice grains via the following mechanisms: Firstly, high temperature can shorten the grain filling period, resulting in insufficient grain filling and inadequate starch accumulation, thus reducing grain yield (Chen et al, 2021b). Secondly, high temperature can reduce the gene expression and bioactivity of key enzymes involved in the conversion of sucrose to starch in endosperm, reducing the rate of starch synthesis and thus affecting total starch content and starch accumulation patterns, especially the amylose content of endosperm starch (Yamakawa and Hakata, 2010;Zhang et al, 2021;Shirdelmoghanloo et al, 2022). Thirdly, high temperature can inhibit photosynthesis in other vegetative organs such as stems and leaf sheaths, resulting in an insufficient supply of fixed carbon from vegetative organs to spikelets, a slower grain filling rate, and a lower grain weight (Yang and Zhang, 2010).…”
Section: Influence Of High Temperature On Maturationmentioning
confidence: 99%
“…High temperature affects starch accumulation in rice grains via the following mechanisms: Firstly, high temperature can shorten the grain filling period, resulting in insufficient grain filling and inadequate starch accumulation, thus reducing grain yield (Chen et al, 2021b). Secondly, high temperature can reduce the gene expression and bioactivity of key enzymes involved in the conversion of sucrose to starch in endosperm, reducing the rate of starch synthesis and thus affecting total starch content and starch accumulation patterns, especially the amylose content of endosperm starch (Yamakawa and Hakata, 2010;Zhang et al, 2021;Shirdelmoghanloo et al, 2022). Thirdly, high temperature can inhibit photosynthesis in other vegetative organs such as stems and leaf sheaths, resulting in an insufficient supply of fixed carbon from vegetative organs to spikelets, a slower grain filling rate, and a lower grain weight (Yang and Zhang, 2010).…”
Section: Influence Of High Temperature On Maturationmentioning
confidence: 99%
“…Previous studies have confirmed that high temperature affects the growth of rice during various developmental periods (Yu et al, 2022), especially during the heading stage (Zhang et al, 2021). In response, various cultivation strategies have been adopted in rice production, including changing the planting method (Xing et al, 2017), adjusting the sowing date (Sadras et al, 2015), and spraying plants with chemical regulators (Cao and Hua, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The steady increase in grain yield, coupled with the rapid improvements in human living conditions, has fostered ever increasing public demands for foods of high quality and high versatility ( Concepcion et al., 2015 ; Huo et al., 2017 ). Consequently, the rice quality, as measured by a range of standardized parameters, including milling, appearance, nutrition and eating and cooking quality (ECQ), has been commonly used to select for and evaluate the breeding lines prior to commercial release ( Zhang et al., 2018 ; Huang X. et al., 2021 ; Hu et al., 2021 ; Zhang H. et al., 2021 ). Amylose and amylopectin constitute starch that is the dominant component in rice grains and accounts for about 90% of the weight of the rice endosperm ( Zhou et al., 2002 ; Wang et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%